Length weight relationship, growth parameter, and condition factor of caroun croaker Johnius carouna (Cuvier, 1830) in the Southern waters of Java - Ria Faizah; Regi Fiji Anggawangsa (Jurnal Iktiologi Indonesia, 2019)
Caroun croaker (Johnius carouna) is one of demersal fishes which are commonly caught in the south of Java waters. This fish captured by trammel net, gillnet, danish seine and mini trawl. This study aims to determine length and weight relationship, growth parameter, length frequency distribution and condition factors of croaker fish caught in the south of Java waters. This study was conducted from January-December 2015 at the Cilacap Ocean Fisheries Port, Central Java. Data collected was total length (TL in mm) and weight (W in g) of caroun croacker fish. A total of 2141 of Caroun croaker was caught by mini trawl during the sampling periods. The result showed that the size of croaker fish caught by mini trawl ranged between 85-225 mm with an average was 143.7 mm. Length and weight relationship expressed by equation of W = 0.0062 TL3.2889 ( R2 = 0.9443). The growth pattern of croaker fish was allometric positive. The Von Bertalanffy growth equation of caroun croacker fish in south of Java waters was Lt =155 (1 - e -0.9(t+0.2127)) with the asymptotic length (L∞) =155 mm, growth coefficient (K) = 0.9 per year and the theoretical age croaker fish that was equal to (t0) = - 0,2127. Abstrak Ikan gulamah (Johnius carouna.) merupakan ikan demersal yang banyak tertangkap di Perairan Selatan Jawa. Ikan ini tertangkap oleh jaring trammel net, payang, gillnet, dan arad. Penelitian ini bertujuan untuk menentukan hubungan panjang bobot, parameter pertumbuhan, faktor kondisi, dan sebaran ukuran panjang ikan gulamah yang tertangkap di Perairan Selatan Jawa. Penelitian ini dilakukan di Pelabuhan Perikanan Samudera Cilacap, Jawa Tengah pada bulan Januari-Desember 2015. Data yang dikumpulkan adalah data panjang dan bobot ikan gulamah. Sejumlah 2141 ekor ikan gulamah yang tertangkap jaring arad telah diamati selama periode sampling. Hasil penelitian menunjukkan bah-wa ukuran panjang total (TL) ikan gulamah yang tertangkap jaring arad berkisar 85-225 mm dengan panjang rata-rata 143,7 mm. Hubungan panjang dan bobot mengikuti persamaan W=0,0062 TL 3,2889 (R2= 0,9443). Ikan gulamah memiliki pola pertumbuhan allometrik positif. Persamaan kurva pertumbuhan Von Bertalanffy ikan gulamah di per-airan selatan Jawa yaitu Lt =155 (1 - e -0,9(t+0,2127)) dengan panjang asimtotik (L∞) =155 mm, koefisien pertumbuhan (K) = 0,9 per tahun dengan umur teoritis (t0) = - 0,2127.